Intensitas Aset Tak Berwujud Memoderasi Pengaruh Modal Intelektual Terhadap Profitabilitas Perusahaan Teknologi - Zacharias, Jems Arison (Value : Jurnal Manajemen dan Akuntansi, 2024)
In the era of knowledge-based economy, the utilization of intellectual capital is very important for the value creation process to increase the profitability of the firm. Therefore, this study aims to examine the effect of intellectual capital on profitability with intangible asset intensity as a moderating variable. Quantitative method with simple and multiple linear regression analysis is used to test the research hypothesis. The population of this study consist of 22 technology firms listed on the Indonesia Stock Exchange (IDX) during the period 2019-2022. The pooled sample was taken using purposive sampling which amounted to 68 firm-year observations. Intellectual capital in this study is measured using Value-Added Intellectual Coefficient (VAIC) while profitability is measured by Return on Asset (ROA). The results of first hypothesis testing are in accordance with the initial prediction that intellectual capital (VAIC) has a positive effect on the profitability of technology sector firms on the IDX. However, the results of the second hypothesis testing are different from the initial prediction because intangible asset intensity does not moderate (strengthen) but instead moderates (weakens) the positive effect of intellectual capital (VAIC) on profitability. This means that the greater the value of intangible asset intensity in the statement of financial position, the smaller the positive effect of VAIC on profitability.